Psychometric Properties of Indonesian Version of Teacher Classroom Management Efficacy Scale - Pramesti Pradna Paramita; Umesh Sharma; Angelika Anderson; Stella Laletas (Psympathic : Jurnal Ilmiah Psikologi, 2023)
Teacher self-efficacy (TSE) in classroom management is an important predictor of teaching practice, but there are limited studies on the application in Asian countries, particularly Indonesia. Therefore, this study aimed to describe psychometric properties of Classroom Management Efficacy scale in Indonesian version. Psychometric properties of the scale were evaluated using a total of 582 Indonesian teachers, who served as participants. The results supported a bifactor model with high internal consistency, showing that the scale could be psychometrically sound measure of TSE in classroom management in Indonesian version.